Knowledge of Diabetes Mellitus Patients in Insulin Injection - Mardana, Amanda Hafidz; Wiga A, Sandi Alfa; Fernandes, Angelina (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2025)
Diabetes Mellitus patients’ awareness of the implementation and compliance with insulin therapy was influenced by several factors that affected treatment success and the risk of complications due to insulin injections. This study aims to determine the level of knowledge regarding insulin injections at Srengat Regional Hospital. The research employed an analytical method with a descriptive approach. The study population consisted of 30 patients with Diabetes Mellitus undergoing insulin injection therapy. The sampling technique used was accidental sampling, resulting in a sample size of 23 patients. The results showed that more than half of the respondents had a good level of knowledge about insulin injections, with 15 respondents (65%) falling into this category. Meanwhile, five respondents (22%) had a moderate level of knowledge, and three respondents (13%) had a low level of knowledge. The level of knowledge significantly influenced patient behavior. Good knowledge of insulin injections was associated with a higher success rate in diabetes mellitus therapy, as it contributed to proper injection practices. This study highlighted the importance of patient and family involvement in the treatment of Diabetes Mellitus, particularly in ensuring correct insulin injection practices.